EKSISTENSI PERMUKIMAN DAN GEOGRAFIS MUARA MAHAKAM (LIPI Press, 2023)
This research aims to examine the geographic conditions of Mahakam Estuary and its relation to the existence of settlements, the forms and development of settlements, and the factors that cause settlements to be concentrated in the Mahakam Estuary area. This research uses a qualitative descriptive method. Data is collected through interviews, observations, documentation, and literature studies. The snowball sampling technique is used to obtain in-depth information and data. This research uses spatial analysis overlay support in creating settlement development maps. Data validation is done using the triangulation technique. The sedimentation process of the Mahakam River forms an elongated delta (bird−foot) shape. The community widely uses the Mahakam Delta area as fishponds, agricultural land, and settlements. The houses are built on stilts and permanent structures. The morphology of settlements includes elongated, clustered, dispersed, linear following transport routes, and surrounding certain facilities. The settlements grew from Kutai, Dayak, and Bugis ethnic villages that migrated. The concentration of the population in the Mahakam Estuary area is influenced by the availability of job opportunities, adequate infrastructure, security, gentle topography, location close to the city, and abundant natural resources potential.